Modeling Electrical Activity of a Neuron: A Bond Graph Approach - Ghasemi, Mojtaba; Eskandari, Faezeh; Hamzehei, Bahareh; Arshi, Ahmad Reza (CMBES Proceedings, 2016)
In many neurological diseases, cell bioelectrical activity is disturbed. This disorder can be caused by changes in the number of neural cell or physical, chemical and electrical properties of cell. Neural tissue modeling can be used to characterize which cell property variation leads to change in neural tissue activity and thus the disease. For a model of neural tissue, the fundamental step is to have a model of single neuron. Therefore, the purpose of this study was to model a neuron and investigate its behavior under initial excitation. Bond graph method was used to develop the neural model based on cable theory and the numerical values resulting from cellular electrophysiology experiments. Initial excitation was applied by means of step and square current functions. Eventually, action potential made along the neuron for both initial excitations was estimated. Changing in the density of ion channels which might leads to some neuropathy was considered to study its effect on action potential alterations, and the results were compared for six different densities. This evaluation revealed that the model developed in this study has the ability to distinguish between different levels of ion channel density.